Stochastic Inventory Control Systems with Consideration for the Cost Factors Based on EBIT - Kenichi NAKASHIMA; Thitima Sornmanapong; Hans Ehm; Geraldine Yachi (International Journal of Supply Chain Management, 2014)
Semiconductor manufacturing in the current world is more competitive than ever/ is extremely competitive. Due to a short market life-span and high uncertainty in future demand, Supply chain management is a competitive advantage which plays an important role in today`s global semiconductor industry. A very important consequence of uncertain demand and having long lead time is the great risk of incurring shortages and excessive inventory. This paper con-siders the view of the second tier semiconductor supplier in automotive industries and studies, using the periodic review analysis, a single item single stage inventory system with sto-chastic demand. The values of s (reorder point) and Q (order quantity) are the two decisions required to implement the policy. The lead time is assumed known and constant. The only uncertainty is associated with demand. Assuming hold-ing, production, salvage and backorder costs, we determine the optimal numerical value of the level s (reorder point) using a simulation approach, and thus define the optimal inventory policy to minimize the total expected inventory cost while being able to achieve the desired customer service levels.